Developing A Business Plan for Micro Powdered Spice Enterprises - Attamimi, Muniroh; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2025)
Herbi, a micro-enterprise offering powdered Indonesian spices, faces several challenges due to the absence of structured business planning. This study aims to design a comprehensive business plan to address issues in production, marketing, finance, and operations. Using a descriptive qualitative research method, data were collected through observation, interviews, and literature review. A purposive sampling technique was applied to select six informants, including customers, potential customers, and owners of similarly scaled spice businesses. The study was conducted in Malang, East Java. Findings reveal that a lack of planning led to inefficiencies and reactive decision-making. The formulated strategy includes product development, optimization of distribution channels, integration of digital tools, and clear financial and organizational planning. The proposed plan demonstrates potential for investment feasibility and operational improvement. This study contributes a practical model for business planning that can serve as a reference for other micro and small powdered spice enterprises aiming to adopt more adaptive, efficient, and growth-oriented strategies.